CIDADES MÉDIAS NA AMAZÔNIA: AMPLIANDO PERCEPÇÕES SOBRE A RESPONSABILIDADE TERRITORIAL DE PARINTINS, AM, BRASIL (Terr@ Plural, 2019)
We aim to incorporate new dimensions into the discussion hitherto held in the construction of the notion of territorial responsibility. In order to do so, we inserted three strands that indicate the importance of Parintins in the Amazonian sub-regional territorial system. For this, the concept of the Urban-Riverside Territorial System (STUR) and its methodological proposal are added. The first is related to the presence of institutions in the city, providing other forms of social organization such as organized collectives that benefit from this density of territorial relations, emphasizing the role of political mediation. The second refers to the role of Parintins as a consolidated sub-regional commercial distributor through the strengthening of commercial companies and territorial river distribution systems. Finally, the environmental responsibility that occurs due to the intensification of regional product absorption by the city related to the main existing territorial systems in the city: timber and fishing.